Exploring the Relationship Between Socioeconomic Elements and Preparedness Intention on the Dam Failure Flood Risk Among Community: A Framework Review - Samsuddin S.A.; Kaman Z.K.; Husin N.M.; Khanm T.; Ali Z.; Harun N.H. (Springer Science and Business Media Deutschland GmbH, 2024)
This research aims to review the literature and previous studies on the relationship between socioeconomic characteristics and community readiness for dam failure flood risk. A systematic literature review (SLR) was done to investigate the association between socioeconomic characteristics and community preparedness intentions for dam failure flood risk. Using keywords such as preparedness intention, dam failure, flood risk, and socioeconomic factors, a complete search of relevant databases, including Scopus, Sciencedirect, and Google Scholar, was done. According to the literature, socioeconomically deprived areas are frequently more exposed to the effects of dam failure due to a lack of resources and information. On the other hand, wealthier areas may have more significant resources and access to knowledge, resulting in higher readiness levels. Education, money, and access to resources have also been proven to be essential determinants in dam failure preparedness intention. As a result of our research, we propose a framework that takes into account a variety of socioeconomic factors, such as age, race and gender, income and occupation, education and knowledge, past experience, and house ownership and location, to provide a more comprehensive understanding of the relationship between these factors and preparedness intention. This approach recognizes that the relationship between socioeconomic determinants and preparedness intention is complicated and may vary depending on the unique environment. As a result, this framework provides a more comprehensive way to analyze the relationship between socioeconomic determinants and community readiness for dam failure flood risk. The Author(s), under exclusive license to Springer Nature Singapore Pte Ltd. 2023.